Distrffiution and Population Structure of Amentotaxus assamica Ferguson, a Critically Endangered and Endemic Species in Arunachal Pradesh - Das, A. K.; Nath, P. C.; Khumbongmayum, A. D. (Indian Forester, 2010)
Amentotaxus assamica, belonging to family Taxaceae, is a critically endangered and endemic species in Arunachal Pradesh, a state in northeast India. Recently, during the field trips in 2005 for the collection and documentation of plant species, Amentotaxus assamica is collected from the forest of Turoo hill, located near Dev village, Papum Pare district. The plant is found growing within the patches of Chimnobambusa sp., a spiny bamboo species occurring abundantly in the Turoo hill. Studies on population structure of A. assamica reveals that density of seedling (220 ha-1) is higher than saplings (58 ha-1) and trees ( 4 7 ha-1). A total of 13 associated tree species were recorded and their density ruld basal area were determined. No anthropogenic threats were observed in the present natural habitat.